2000
DOI: 10.1093/bja/85.3.482
|View full text |Cite
|
Sign up to set email alerts
|

The Reflector: a new method for saving anaesthetic vapours

Abstract: Anaesthesia systems that minimize the use of volatile anaesthetics to reduce cost and pollution are of interest. Closed circuit anaesthesia is the ideal solution, but requires continuous adjustment of fresh gas flow and composition and thus is demanding in routine practice. We describe an alternative system, the Reflector system, which is open in regard to oxygen, nitrogen and N2O, and semiclosed in regard to volatile anaesthetics. The Reflector system is a circle system with a carbon dioxide absorber and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
(2 reference statements)
0
13
0
1
Order By: Relevance
“…To the authors’ knowledge, no reports are available about factors, which may increase anaesthetic agent breakthrough with the AnaConDa device. It has been shown that isoflurane breakthrough through zeolite filters, was more pronounced at higher (Perhag et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors’ knowledge, no reports are available about factors, which may increase anaesthetic agent breakthrough with the AnaConDa device. It has been shown that isoflurane breakthrough through zeolite filters, was more pronounced at higher (Perhag et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, a filter containing hydrophobic zeolite was used, reducing the isoflurane consumption by 50–70% compared with a conventional open system (Thomasson et al. 1989; Perhag et al. 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial attempts at conserving anaesthetic vapours using an open system involved the development of a reflector which incorporated zeolite crystals. [1516] However, this was subsequently abandoned due to the possibility of zeolite inhalation causing pulmonary toxicity.…”
Section: Technical Prerequisites For the Use Of Volatile Anaestheticsmentioning
confidence: 99%
“…Alternativ sind auch die Bezeichnungen Anästhesiegasreflektorsystem oder Anästhesiegaskonservierungsfil-ter gebräuchlich [32]. Der aktuelle Wissenstand der Anwendung volatiler Substanzen unter intensivmedizinischen und organprotektiven Gesichtspunkten wird dargestellt.…”
Section: Analgosedierungunclassified